Modern methods of auditing and monitoring tasks in information security - Чунарьова, А. В. (Problems of Informatization and Control, 2013)
The article presents the classification and analysis of existing methods of auditing and monitoring ofinformation flows of information and communication systems and networks, which permitted theformation of the criteria for assessing the quality of monitoring systems.